O/N/S trifunctional doping on graphite felts: A novel strategy toward performance boosting of cerium‐based redox flow batteries - Zhaolin Na; Xinran Wang; Xiaoting Liu; Wenjing Li; Xudong Sun (Carbon Energy, 2021)
Abstract The cerium‐based redox flow battery (RFB) is regarded as a compelling grid‐scale energy storage technology to revolutionize the utilization of renewable energy by storing the energy in liquid electrolytes. However, its widespread implementation is impeded by the cerium redox reactions that exhibit slow kinetics on commercial graphite felt (GF) electrodes. Surface functionalization may be an available activation strategy to achieve a significant boost in the electrochemical performance of GFs. However, conventional chemical and/or electrochemical routes for the surface functionalization of GFs suffer from the issues of complication, and the deterioration of the resulting modified electrode surface over long‐term cycle processes leads to catalytic activity decline. Here, we develop a facile and general strategy for introducing the functional groups to the electrode through the addition of l‐cysteine into electrolytes. The –COOH, –NH2, and –SH groups in l‐cysteine can induce oxygen/nitrogen/sulfur trifunctional doping on GF surfaces with lower deterioration rates, which enables the activated GFs to demonstrate a promising electrocatalytic activity toward cerium redox reactions and excellent durability when used as a cerium‐based RFB electrode. This study proposes a rational strategy to overcome the intrinsic limitations of existing modification techniques for GFs and provides a potential pathway toward high‐performance RFBs.